Date of pruning in upland cotton cultivars - Azevedo, Demóstenes Marcos Pedrosa de; Beltrão, Napoleão Esberard de Macedo; Nóbrega, Laudemiro Baldoino da; Crisóstomo, João Ribeiro (Pesquisa Agropecuaria Brasileira, 2014)
A variety trial of seven upland cotton cultivars (G. hirsutum L.) was conducted during 1979 and 1980 in the Rio Piranhas valey, in the State of Paraíba, Brazil, to study their performance under two different pruning dates. The results showed that: 1º) pruning must be done before the rainy season; 2º) the highest yielding cultivars, in terms of total yield for the two years combined, were the same cultivars that, when pruned, showed better perfomance ('AlIen 333/57', 'SU 0450/8909', 'CNPA 78/5B' e 'Reba B-50'); and 3º) in relation to technological and agronomic fiber characteristics, only the character 100-seeds weight was affected by the date of pruning factor.